Comparative anatomic analysis of leaves of Lonicera tatarica and Lonicera microphylla - Gavrilkova, E.; Tleukenova , Saltanat; Ageev, Dmitry; Ramazanov, A. (Fundamental and Experimental Biology, 2025)
The study of anatomical structure of vegetative organs of plants allows to estimate biological and ecological features of species and to reveal features of structure, which allow to carry out identification of taxa at microscopic level. This is especially important for taxonomically close species. The paper presents the results of a comparative anatomical study of leaves of Lonicera tatarica and Lonicera microphylla. Leaf samples were collected in the summer period of 2024, fixed in Strauss-Fleming's solution, surface preparations and transverse sections were made manually. The results of the studies allowed us to establish that both honeysuckle species are characterized by light leaves, of dorso-ventral type with differentiated mesophyll into columnar and spongy tissues. Stomata are few, of anomocytic type, localized mainly on the underside of the leaf. In both species, small rounded druzes of calcium oxalate are present. Differences between the species were found in the shape of leaf epidermal cells, the number of columnar and spongy tissue layers, the shape of conductive bundles, the number of calcium oxalate druses and the presence of simple trichomes.